2016
DOI: 10.3847/0004-637x/832/1/55
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Irradiation-Driven Hydrogen Isotope Fractionation in Analogs of Protoplanetary Hydrous Silicate Dust

Abstract: The origin of hydrogen in chondritic components is poorly understood. Their isotopic composition is heavier than the solar nebula gas. In addition, in most meteorites, hydrous silicates are found to be lighter than the coexisting organic matter. Ionizing irradiation recently emerged as an efficient hydrogen fractionating process in organics, but its effect on H-bearing silicates remains essentially unknown. We report the evolution of the D/H of hydrous silicates experimentally irradiated by electrons. Thin fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…The amplitude of the fractionation for =0.5 is of several hundreds of ‰. Such a large diffusion-driven fractionation was indeed recently produced experimentally by electron irradiation of hydrous analogues of the dust present in the protoplanetary disk (Roskosz et al, 2016).…”
Section: Modelling Diffusion-driven D/h Fractionation In Glasses Melmentioning
confidence: 81%
See 1 more Smart Citation
“…The amplitude of the fractionation for =0.5 is of several hundreds of ‰. Such a large diffusion-driven fractionation was indeed recently produced experimentally by electron irradiation of hydrous analogues of the dust present in the protoplanetary disk (Roskosz et al, 2016).…”
Section: Modelling Diffusion-driven D/h Fractionation In Glasses Melmentioning
confidence: 81%
“…Nevertheless, molecular hydrogen diffusion also occurs in more exotic environments, namely i) in very reducing conditions, ii) when the hydrogen fugacity (f H2 ) is high, iii) when radiolysis occurs in situ, for instance during ionizing irradiation of silicates. The last process was recently found efficient to separate D and H of water (and hydroxyl) groups dissolved in amorphous and crystalline silicates (Roskosz et al, 2016). For this reason, we provide models describing the spatial redistribution of H and D, in an amorphous silicate, caused by the diffusion of either molecular water or hydrogen atoms ( Fig.…”
Section: Modelling Diffusion-driven D/h Fractionation In Glasses Melmentioning
confidence: 99%
“…During accretion, localized irradiation processes within 3 AU could not have modified the primitive hydrogen signatures of the NAMs ( 42 ). Therefore, the accreted pebbles from the NAMs and planetesimals would preserve the D/H ratio acquired during formation in agreement with our observations: Itokawa, Earth, and parent bodies of LAR 12036 and Bishunpur ordinary chondrites, all formed in the inner solar system and exhibit comparable D/H ratios.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that D/H ratios in silicate minerals freely floating in the protosolar nebula prior to accretion or on the surface of the parent bodies are modified by electron irradiation. Previous experiments by Roskosz et al (2016) reported that electrons in the keV regime have the capacity to produce large D-enrichment (fractionation of D/H can be up to 600‰) in analogs of insoluble organic matter that is present in chondrites. However, the electron irradiation effects on silicate minerals are shown to be much smaller (fractionation of D/H is <200‰).…”
Section: A Source Of Low D/h Ratios In Benenitra and Chelyabinskmentioning
confidence: 99%
“…However, the electron irradiation effects on silicate minerals are shown to be much smaller (fractionation of D/H is <200‰). Particularly, fractionation of hydrogen isotopes caused by the electron irradiation in the silicate minerals larger than 10 μm is supposed to be <20‰ (Roskosz et al 2016). In our case, the measured orthopyroxenes in the OCs are all larger than 10 μm in size.…”
Section: A Source Of Low D/h Ratios In Benenitra and Chelyabinskmentioning
confidence: 99%